Indicators for the Compression and Stretching Characteristics of the HTF-Coordinate of WRF - Hailiang Zhang; Huoqing Li; Shuiyong Fan (Advances in Meteorology)
The HTF-coordinate is a feature that has been imported into the Weather Research and Forecasting (WRF) model version 4, and it is important to understand how it can be used efficiently. Indicators are needed to describe the characteristics of the distribution of the vertical coordinate and to evaluate the rationality of the configuration of the HTF-coordinate. Such indicators, including the maximum factor of compression (MFC), eta corresponding to the MFC, and the critical point of compression (CPC), were defined and calculated in this study. The indicators were also validated to efficiently and accurately describe the characteristics of the distribution of the vertical coordinate of the WRF model. They constituted the integrated system to resolve the problem of the configuration of the HTF-coordinate of WRF. The nonmonotonicity, compression, and stretching that were caused by the nonlinearity of the HTF-coordinate were also illustrated and validated.